The New Comparative Economics - Djankov, Simeon; Glaeser, Edward; La Porta, Rafael; Lopez-de-Silanes, Florencio; Shleifer, Andrei (World Bank, Washington, DC, 2014)
In recent years, comparative economics experienced a revival, with a new focus on comparing capitalist economies. The theme of the new research is that institutions exert a profound influence on economic development. The authors argue that, to understand capitalist institutions, one needs to understand the basic tradeoff between the costs of disorder and those of dictatorship. They then apply this logic to study the structure of efficient institutions, the consequences of colonial transplantation, and the politics of institutional choice.